An innovative small-scale prototype plant integrating a solar dish concentrator with a molten salt storage system. (August 2018) - Turrini, Sebastiano; Bettonte, Marco; Eccher, Massimo; Grigiante, Maurizio; Miotello, Antonio; Brusa, Roberto S.
Abstract: An innovative plant configuration joining a thermal energy storage device with a 2 kWTh parabolic solar dish collector (PDC) has been designed. The novelty of this small-scale solar plant prototype consists in the use of molten salts (MS) both as fluid carrier and thermal energy storage medium. An eutectic mixture of NaNO3, NaNO2 and KNO3 has been used allowing a 10 kWh energy storage accomplished with two 50-L tanks. An experimental campaign has been planned to test the behavior of each of the assembled components and to provide a preliminary analysis of the plant performances. As first evaluation, the energy efficiency of the system has been calculated in correspondence to selected MS flow rates referred to steady state conditions. This has been achieved by monitoring the MS temperature in correspondence to suitable points of the inlet and outlet sections of the receiver. The preliminary confirmations of this investigation looks promising to integrate the PDC technology within district heating systems for advanced renewable energy exploitations. Graphical abstract: Image 1 Highlights: A molten salt energy transfer and storage system was built and coupled to a small parabolic dish. Hitec ® salt was used as transfer and storage fluid. Heat transfer performances were experimentally tested.